2014
DOI: 10.1515/ijamh-2013-0324
|View full text |Cite
|
Sign up to set email alerts
|

Health-promoting lifestyle and its predictors among Iranian adolescent girls, 2013

Abstract: The findings show that adolescents "sometimes" or "often" show health-promoting behaviors. In addition to self-efficacy as the main predictor, some of the socio-demographic characteristics are also among the predictors of health behaviors. With consideration of adolescence years as a foundation for one's future life, it is necessary to provide strategies to encourage a health-promoting lifestyle in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
0
16
1
1
Order By: Relevance
“…In this study, the mean overall score of health-promoting behaviors was moderate (M = 2.40), which was equal with the study conducted on infertile women (M = 2.40) in Tabriz, Iran (24). However, it was lower in comparison to the studies conducted on women in reproductive age in Tehran, Iran (21), adolescent girls in Sanandaj, Iran (25), postmenopausal women in Tabriz, Iran (22) and it was higher compared with a study on women with polycystic ovarian syndrome in Urmia, Iran (26). The discrepancy in health-promoting behaviors between this study and previous ones conducted in other cities of Iran could be associated with the effect of disease and the characteristics of the subjects, culture, physical environment, social structure, and promotional activities (27,28).…”
Section: Discussioncontrasting
confidence: 45%
“…In this study, the mean overall score of health-promoting behaviors was moderate (M = 2.40), which was equal with the study conducted on infertile women (M = 2.40) in Tabriz, Iran (24). However, it was lower in comparison to the studies conducted on women in reproductive age in Tehran, Iran (21), adolescent girls in Sanandaj, Iran (25), postmenopausal women in Tabriz, Iran (22) and it was higher compared with a study on women with polycystic ovarian syndrome in Urmia, Iran (26). The discrepancy in health-promoting behaviors between this study and previous ones conducted in other cities of Iran could be associated with the effect of disease and the characteristics of the subjects, culture, physical environment, social structure, and promotional activities (27,28).…”
Section: Discussioncontrasting
confidence: 45%
“…In another study, a significant relationship was found between increased selfefficacy and reduced stress, anxiety, and depression (41). Also, a study conducted on adolescent girls in 2015 showed the positive effect of self-efficacy on improved lifestyle (17). Thus, it is necessary that the counseling sessions regarding promoting self-efficacy be held by health care providers in health centers for all women in different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy means an individual's belief in their ability to face a particular situation (16,17). Today, it is believed that people can successfully change their behavior and improve their health if they see themselves efficient in overcoming barriers to behavior change (18).…”
mentioning
confidence: 99%
“…The 6 dimensions of AHLQ include nutrition (6 items), physical activity (6 items), health responsibility (8 items), stress management (4 items), social support (5 items), spiritual growth and self-actualization (7 items). The total score of AHLQ could range from 36 to 180 and is interpreted as unhealthy (a score of 36 to 84), moderately healthy (a score of 85 to 133), and healthy (a score of 134 to 180) lifestyle (24). Taymoori et al (2012) used AHLQ to assess the health-promoting lifestyle of a group of Iranian adolescents and reported a Cronbach's alpha of 0.82 (22).…”
Section: Methodsmentioning
confidence: 99%